Recognition of Mental Illness As A Consequence of Medical Workers In The Procedure For Claiming Work Accident Insurance In Indonesia - Irma Nafa Nabila; Salsabila Maulida Rahmah; Fajar Rachmad Dwi Miarsa; Rizal Haliman; Danggur Feliks (Journal of International Multidisciplinary Research, 2024)
Medical personnel are a group of workers who are at high risk of experiencing work accidents and occupational diseases. One type of occupational disease that is often experienced by medical personnel is mental illness. Mental illnesses experienced by medical workers can have a negative impact on their quality of life, performance and productivity. Therefore, medical personnel who suffer from mental illness have the right to receive protection and guarantees from the government and employers. However, in practice, medical personnel who suffer from mental illness often experience difficulties in submitting claims. The research entitled "Recognition of Mental Illness as a Consequence of Medical Personnel in Work Accident Insurance Claim Procedures in Indonesia" is normative-qualitative research. Medical workers face a lot of stress and workload, especially during the COVID-19 pandemic, and mental illness is one of the consequences. Mental illness can impair their performance, health, and well-being, and place them at risk to patients and their work environment. With the recognition of mental illness as a consequence of medical personnel in the JKK claim procedure in Indonesia, JKK is a social security program organized by BPJS Employment. This program provides guarantees to workers or laborers to receive health services and cash compensation due to work accidents or work-related illnesses. So it is hoped that it can provide benefits for medical personnel in the form of getting proper protection, increasing the productivity of medical personnel and improving the quality of health services.